Assessment of agar gel loaded with micro-emulsion for the cleaning of porous surfaces - Florence Gorel (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Agar gel loaded with micro-emulsion could be used to extract lipophilic materials from porous surfaces. The physical properties of the gels are good enough for a conservation work. They allow the micro-emulsion to flow on the porous surface and to wet it but maintain the micro-emulsion in its structure and prevent the formation of rings. The evaporation of the solvents is slowed down and the gels can be used during a long period.